Factors associated with time to first birth after marriage: A systematic review (BIBECHANA, 2024)
First birth interval after marriage is a particularly interesting subject, because it unveils both the social behaviors and fertility patterns. Though, for a woman, who marry at an early age and get sooner childbearing can be the health threat for both mother and child. The objective of this study is to systematically investigate significant predictors associated with time to first birth after marriage. Following the PRISMA guidelines; three database Scopus, PubMed and EMBASE were used to capture relevant articles. A total of 21 articles with the thorough assessment of 326 articles published in English up to 10 January 2024 were included in final review. Thirty-nine significant predictors associated with first birth interval after marriage have been explored. Predictors, such as age at marriage, education, residence, contraceptive, religion, wealth index were observed as some of the major significant predictors. The findings indicate to take care of those factors in order to deal with time to first birth after marriage. Understanding the impact of influential factors can be considered as important reference to formulate appropriate policy to intervene effective program as well as to plan such studies based on primary data with special reference to certain country or region.